Linear property and optimal design of MARS-like cryptographic structure - Nianping WANG; Lirong HONG (Tongxin xuebao)
A MARS-like cryptographic structure was proposed and some linear properties of this cryptographic structure were given.An optimal design method of linear transformation in MARS-like cryptographic structure was also given.Concretely, by analyzing the transfer law of a class of linear approximation with special structure, regardless of the selected linear bijection, the existence of the linear approximation with 0 active round function in the t(1≤t≤3) round had been demonstrated.Furthermore, there was at least one with no more than 1, ⌊8t/15⌋ active round function among the 4, t(t＆gt;4)-round of linear approximation, respectively.On this basis, an optimal design method was proposed to make the lower bound of the number of active round function closer to the maximum possible value than the MARS cryptographic structure for the linear transformation in the MARS-like cryptographic structure.